Modeling Physical Inactivity among University of Eldoret Staff in Kenya using a Logit Model - Koech , Julius; Kavila , Willie Mercy (African Journal of Education,Science and Technology (AJEST), 2024)
Physical inactivity (PI) is a significant contributor to non-communicable diseases globally. This study focused on assessing the prevalence of PI among staff at the University of Eldoret and exploring the factors that contribute to it. The goal was to improve staff well-being, thereby enhancing overall organizational output and service quality. The study utilized a descriptive case study design, collected data through self-report questionnaires. The questionnaire covered demographic information, sedentary behaviors, and physical activity. The data were summarized using means and standard deviations, and presented through frequency distribution tables as well as graphical techniques for categorical variables. 321 employees participated in the study. Among female employees, the majority had perfect, good, and average fitness levels compared to male employees (70.4% vs. 29.6%, 80.1% vs. 19.9%, and 70.3% vs. 29.7%, respectively). A similar trend was observed among non-teaching staff compared to teaching staff. The prevalence of PI among employees was 36%, higher than the global prevalence of 25% among adults. The statistically significant factors associated with PI were low monthly income (AOR=0.31, 95%CI=0.1159-0.8351), lack of a physical activity plan (AOR=1.85, 95%CI=1.0877-3.1957), and higher BMI levels (AOR=4.29, 95%CI=1.1156-21.4148). Wealthier individuals had a lower risk of PI, although the association was not statistically significant. The study recommends promoting physical activity awareness and wellness programs in institutions. By identifying influential factors related to PI, the study provides crucial information for decision-making and policy formulation aimed at promoting a more active and healthier lifestyle among employees in similar settings.